Struktur Teks Mantra Pengobatan Masyarakat Melayu di Kabupaten Kuantan Singingi - Piliang, Wilda Srihastuty Handayani; Ningsih, Rika; Fatmawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This research was motivated by efforts to preserve mantras as part of oral literature. Although the treatment spell still exists in Kuantan Singingi district, it does not rule out the possibility that the spell can be extinct in people's lives someday. This study aimed to analyze the language of medication mantras in Kuantan Singingi district through diction, figurative language, and imagery with qualitative descriptive research. Data was collected through field observation techniques, library studies, interviews, and data recording with two shamans who are heirs as a source of data. The mantra in this study was limited to only the mantra of medication in Kuantan Singingi district, namely spells for ubek togak mato, ubek gombung, ubek katoguran, ubek batuak parangan, ubek kuyang, ubek poruik sakik twisted and babunyi, ubek antu aiar, ubek biring. Based on the study's results, it can be known that the diction in the medication spell has a forming structure in the form of the opening, core, and cover parts. All spell diction in the opening part always begins with Bismillahirrahmanirrahim and closes with Laa Ilaha Illallah. The core section contains tabiks, reverences, or supplications; statement or confession; exclamation; orders, prohibitions, or statements of intent; and oaths and punishments. Figurative language in the mantras of medication were metaphors, personifications, epithets, and antonomasia. Imagery in the mantras of medication was the imagery of vision, hearing, touch, and motion.